2012
DOI: 10.1002/rem.21312
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of metals in active cap materials: A laboratory and numerical evaluation

Abstract: 9Active capping involves the use of capping materials that react with sediment contaminants to 10 reduce their toxicity or bioavailability. Although several amendments have been proposed for use 11 in active capping systems, little is known about their long-term ability to sequester metals. 12Recent research has shown that the active amendment apatite has potential application for metals 13 contaminated sediments. The focus of this study was to evaluate the effectiveness of apatite in 14 the sequestration of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…As was expected, all cap materials prevented desorption of metals from the underlying sediment over the six‐month period represented by the study. These data are in agreement with model predictions, which show that even sand will retain metals in sediment for one year in the absence of transport mechanisms other than diffusion (Dixon & Knox, ; Knox et al., ). Over longer periods, the metal binding capacity of active sequestering agents becomes critical, and it significantly retards the release of sediment contaminants compared with inert materials such as sand (Dixon & Knox, ; Knox et al., ).…”
Section: Resultssupporting
confidence: 87%
“…As was expected, all cap materials prevented desorption of metals from the underlying sediment over the six‐month period represented by the study. These data are in agreement with model predictions, which show that even sand will retain metals in sediment for one year in the absence of transport mechanisms other than diffusion (Dixon & Knox, ; Knox et al., ). Over longer periods, the metal binding capacity of active sequestering agents becomes critical, and it significantly retards the release of sediment contaminants compared with inert materials such as sand (Dixon & Knox, ; Knox et al., ).…”
Section: Resultssupporting
confidence: 87%
“…A second experiment highlighted that the reactive materials limited Pb, Zn, Ni, Cr, and Cd potentially mobile fractions. These results were in agreement with the model simulations that showed that even sand can retain metals in sediment for one year in presence of only diffusion phenomenon (Dixon and Knox, 2012). However, in the long-term the metal binding capacity of reactive materials became crucial and they considerably retarded the release of pollutants compared with sand (Knox, Paller and Roberts, 2012b).…”
Section: Isc Amendments For Inorganic Contaminationsupporting
confidence: 90%
“…Both sediments and seawater samples were chemically characterized with EPA standard method 8275A. The column experiments were set up following the same methods used by U.S. Army Corps of Engineers (1987) and several researchers (Gidley et al, 2012;Dixon and Knox 2012;Silvani et al, 2017). Pyrene, benzo[a]pyrene and anthracene concentrations were equal respectively to 898, 519…”
Section: Evaluation Of Short-term Adsorption Efficacy Of Two Reactivementioning
confidence: 99%